Effects of initial nutritional status on the responses to a school feeding programme among school children aged 6 to 13 years in the Millennium Villages Project, Siaya, Kenya - Masibo, Peninah Kinya (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.